A commentary on the Pan American Network of Nursing and Midwifery Collaborating Centres - Madeline A. Naegle; Andrea Baumann; Danielle Denwood (Pan American Health Organization, 2023)
This article provides a commentary on the Pan American Network of Nursing and Midwifery Collaborating Centres (PANMCC). The objectives are to present an overview of the formation and evolution of the network, its impact on education, research, policy and communication and the benefits of membership. The advantages of international networks as a mechanism to strengthen nursing and midwifery workforces and improve health systems are also highlighted. The Pan American Health Organization (PAHO), the World Health Organization (WHO) Office in the Americas, oversees collaborating centres in the Region. Established in 1999, PANMCC consists of 17 centres situated in universities and schools of nursing. These centres provide crucial nursing and midwifery input to PAHO/WHO. The network supports global engagement and capacity building via collaboration, resource sharing and research colloquia. The linkages within the network enhance professional development, increase capacity building and heighten visibility of PANMCC and the work of its members.